2018
DOI: 10.1029/2017gc007314
|View full text |Cite
|
Sign up to set email alerts
|

Deep Resistivity Structure of Basalt‐Covered Central Part of Paraná Basin, Brazil, From Joint 3‐D MT and GDS Data Imaging

Abstract: The deep structure beneath the basalt‐covered sediments of Paraná basin is not well understood. Magnetotelluric (MT) broadband (1,000 to 0.001 Hz) data recorded at 296 selected stations along three new survey lines were first inverted in three dimensions to reveal the local scale resistivity structure of the central part of the basin where there are three deep exploration wells with resistivity logs for model validation. The 3‐D MT inversion model correctly identified the resistive (>100 Ωm) flood basalts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Although structures outside of the data area should be interpreted with caution, this conductor is robust, since it appeared in every inversion we run, using different initial models and parameters, and was also suggested by the induction arrows behavior in this part of the profile, where they point northwestwards. In Brazil, other MT and GDS studies conducted by PADILHA et al (2015) and MAURYA et al (2018) have shown a similar conductive lineament continuing to the northeast, from the Argentina-Brazilian border on. In Brazil it is close to the basin depocenter, coincident to areas where the basalt layer is thicker.…”
Section: Groom-baileysupporting
confidence: 53%
See 1 more Smart Citation
“…Although structures outside of the data area should be interpreted with caution, this conductor is robust, since it appeared in every inversion we run, using different initial models and parameters, and was also suggested by the induction arrows behavior in this part of the profile, where they point northwestwards. In Brazil, other MT and GDS studies conducted by PADILHA et al (2015) and MAURYA et al (2018) have shown a similar conductive lineament continuing to the northeast, from the Argentina-Brazilian border on. In Brazil it is close to the basin depocenter, coincident to areas where the basalt layer is thicker.…”
Section: Groom-baileysupporting
confidence: 53%
“…In Brazil it is close to the basin depocenter, coincident to areas where the basalt layer is thicker. Maurya et al (2018) have proposed a deflection of this conductive lineament to the east at latitude ~28S, towards the Torre Syncline. Our inverted model suggests another possibility, that it continues directly into Argentina.…”
Section: Groom-baileymentioning
confidence: 99%
“…In this case, the modeled geoelectric values should be considered lower estimates of potential real values. However, within the basin, MT surveys (e.g., Maurya et al., 2018; Padilha et al., 2015) show that the volcanic‐sedimentary package is quite homogeneous in terms of electrical resistivity, approaching a 1‐D situation. Variations in the geoelectric field occur mainly in the crystalline basement under the basin and are correctly represented in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Although much MT work has been completed in the areas of Brazil and India that were affected by these recent flood-basalt events (e.g., Danda et al, 2017;Maurya et al, 2018;Padilha et al, 2015;Patro & Egbert, 2011), all studies so far have focused on crustal and uppermost mantle structures (even though resolvable resistive structures in some cases do extend deeper, beyond the putative depth resolution limit), and there are few three-dimensional inversion results from these areas. Current MT results are insufficient to make a clear comparison between MT-derived and seismic-derived estimates of thermal lithosphere properties in those regions.…”
Section: Discussionmentioning
confidence: 99%
“…Current MT results are insufficient to make a clear comparison between MT-derived and seismic-derived estimates of thermal lithosphere properties in those regions. Although much MT work has been completed in the areas of Brazil and India that were affected by these recent flood-basalt events (e.g., Danda et al, 2017;Maurya et al, 2018;Padilha et al, 2015;Patro & Egbert, 2011), all studies so far have focused on crustal and uppermost mantle structures (even though resolvable resistive structures in some cases do extend deeper, beyond the putative depth resolution limit), and there are few three-dimensional inversion results from these areas. Further work in these regions, as well as in other regions affected by CAMP magmatism (specifically the margins of Europe, Africa, and northeastern North America) is clearly warranted to see if similar apparent discrepancies between seismic and MT observations are found.…”
Section: Discussionmentioning
confidence: 99%